The authority of the sunnah and its applications in financial transactions - Zamri, Muhammad Faiz Iqmal; Nor Hishamuddin, Nuraqilah; Razali, Noor Syuhana; Azahar, Noor Ameera Asya; Mohd Kamil, Nur Anis Syahirah (2025)
The sources of Islamic law are everything that generates the law that governs Muslims on God's earth. The source of law is the primary source, which is the law that society, especially Muslims, must adhere to. This source of legislation means the Book of God relating to the actions and behaviour of the accountable person, whether by request, choice or trust. This means that every action or behaviour performed by society is subject to a law, whether it is a law of obligation, disliked, forbidden, or obligatory. Legal sources are divided into two types: legal sources agreed upon by scholars, and legal sources not agreed upon by scholars. The sources of law agreed upon by scholars are the Qur'an, Sunnah, consensus, and analogy, while the sources of law scholars disagree on, such as istihsan, istihsan, istislah, masalih al-mursala, custom, and the like. Hadith is one of the sources of legislation agreed upon by scholars, which Muslims need to apply in their daily lives. Hadith is the second source for Muslims after the Holy Quran. The teachings contained in this hadith can be practiced as a form of obedience in emulation of the Prophet Muhammad, peace be upon him (Abdul Fattah 2019). Hadith can also be used to determine the law in action and solve problems related to laws. This hadith covers various aspects as it does not only relate only to transactions but also to worship, disputes, crime, and so on. As Muslims, we are required to carry out the commands contained in the two main sources of Islam, which are the Qur'an and the Sunnah. This hadith is also very important for Muslims because it introduces a new law that is not mentioned in the Qur'an . This means that there are many things that are included in the law of governance that are not mentioned in detail in the Qur'an, but the hadiths come to clarify and reveal them. For example, the manner of performing prayer, which Allah, the Almighty, commanded in the Qur'an, but did not mention or explain in further detail. This matter is then explained through the hadith of the Prophet Muhammad, peace be upon him.